Relações de poder, políticas e conflitos territoriais: a negação de direitos dos indígenas e afrodescendentes na Costa Caribe nicaraguense ‒ América Central - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This thesis presents an ethnographical discussion about political-territorial conflicts and power relations in the North and South Caribbean Coast Autonomous Region of Nicaragua, Central America. Such relations are closely tied to the State of Nicaragua and demonstrate its position before territorial rights and the self-determination of the Indigenous peoples and so-called “Afro-descendants” that inhabit this region. In order to analyze the dynamics of these relationships, ethnographical data was collected in reference to the megaproject known as the "Gran Canal Interoceánico" (Inter-oceanic Canal), primarily the socioenvironmental impacts that it will have on those Caribbean peoples, as well as the so-called "campesinos" from other Nicaraguan regions. With the intent to deepen the concerning ethnographical discussion, which is also directly connected to the demarcation stage classified as the "saneamiento" (territorial “sanitation”), a more prolonged anthropological investigation in the field was conducted in the North Caribbean Region, in the territory that belongs to the Miskitu indigenous people, titled "Wangki Twi-Tasba Raya", specifically in the indigenous communities "Wisconsin", "La Esperanza-Río Wawa", "Santa Clara" and" Francia Sirpi". This was because of the more intense situation of conflict in this territory, which calls attention to the extreme violence instigated between indigenous and non-indigenous peoples due to territorial disputes: a circumstance that shows State negation in regard to taking action through and guaranteeing ethnically differentiated laws, which encompass the fundamental rights of the peoples originally from the Nicaraguan Caribbean Coast. This study also approaches the data collected from an interdisciplinary perspective, based on analytical instruments used in anthropology, sociology, history, geography and political science, with the objective of reflecting about the indigenous movement and ethnic mobilizations in the Americas, especially in Central America.
Relations of Power, Politics and Territorial Conflicts: the denial of rights of the Indigenous and Afro-descendant peoples in the Nicaraguan Caribbean Coast – Central America
Relaciones de poder, políticas y conflictos territoriales: la negación de derechos de los indígenas y afrodescendientes en la Costa Caribe nicaragüense ‒ América Central
Keywords: Direito dos povos indígenas; Conflitos político-territoriais; Indígenas da América Central; Indígenas Miskitu; Afrodescendentes - Nicarágua; CIÊNCIAS HUMANAS; Movimento Indígena; Mobilização Étnica; Conflitos Territoriais; Relações Políticas e de Poder; Autonomia; Estado